2015
DOI: 10.1080/07380569.2015.1004278
|View full text |Cite
|
Sign up to set email alerts
|

Examining the Enactment of Web GIS on Students' Geospatial Thinking and Reasoning and Tectonics Understandings

Abstract: Geospatially enabled learning technologies may enhance Earth science learning by placing emphasis on geographic space, visualization, scale, representation, and geospatial thinking and reasoning (GTR) skills. This study examined if and how a series of Web geographic information system investigations that the researchers developed improved urban middle-school learners' GTR skills and their understanding of tectonics concepts. Paired-sample t tests for analyses of tectonics content knowledge and GTR achievement … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…The manipulation of the Web GIS maps required for this curriculum was a new way of learning for most students as many had never used dynamic maps in other courses. Research has shown that using Web GIS embedded into a curriculum increases spatial thinking skills and helps students develop GSTR skills (Bodzin, Fu, Bressler, & Vallera, 2015;Bodzin, Fu, Kulo, & Peffer, 2014;Lee & Bednarz, 2009;Reed & Bodzin, 2016). Results from this research study supports prior findings that demonstrated significant mean differences in SHOM and GSTR skill attainment when using the geospatial curriculum approach.…”
Section: Discussionmentioning
confidence: 99%
“…The manipulation of the Web GIS maps required for this curriculum was a new way of learning for most students as many had never used dynamic maps in other courses. Research has shown that using Web GIS embedded into a curriculum increases spatial thinking skills and helps students develop GSTR skills (Bodzin, Fu, Bressler, & Vallera, 2015;Bodzin, Fu, Kulo, & Peffer, 2014;Lee & Bednarz, 2009;Reed & Bodzin, 2016). Results from this research study supports prior findings that demonstrated significant mean differences in SHOM and GSTR skill attainment when using the geospatial curriculum approach.…”
Section: Discussionmentioning
confidence: 99%
“…This research explored the possibility of using Google Maps in teaching and understanding specific Earth science concepts and the reception of its utilization among students. Earlier studies have shown that Earth science learning may be improved by geospatially-enabled learning technologies that highlight geographic visualization, scale, representation, and geospatial thinking and reasoning (Bodzin et al, 2014;Bodzin et al, 2015). Specifically, this study explored the use of Google Maps in observing and inferring the possible locations of surface features associated with faults.…”
Section: Framework Of the Studymentioning
confidence: 99%